Towards a framework for pastoral systems research - Haan, Cees de (International Livestock Centre for Africa, 1983)
Describes the dif. phases in the ILCA research framework, w. regard to Livestock Systems Research (LSR), particularly the descriptive, diagnostic, design, testing & extension phases, using examples of field research on pastoral & agropastoral systems in the arid & semi arid zones of Mali, Ethiopia and Kenya.